2019
DOI: 10.1112/s0025579319000044
|View full text |Cite
|
Sign up to set email alerts
|

New Results on Sum‐product Type Growth Over Fields

Abstract: We prove a range of new sum-product type growth estimates over a general field F, in particular the special case F = F p . They are unified by the theme of "breaking the 3/2 threshold", epitomising the previous state of the art.This concerns two pivotal for the sum-product theory questions, which are lower bounds for the number of distinct cross-ratios determined by a finite subset of F, as well as the number of values of the symplectic form determined by a finite subset of F 2 .We establish the estimate |R[A]… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 55 publications
(150 reference statements)
2
75
0
Order By: Relevance
“…Theorem 3 enables one to improve upon (4). This can also be viewed as the special case of the general open question, concerning the minimum cardinality of set of values of the symplectic form on pairs of points in a given set in the plane F 2 (here the set being A × A), see [MPORS,Theorem 4] for a general geometric bound. We formulate the next theorem in slightly more generality.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Theorem 3 enables one to improve upon (4). This can also be viewed as the special case of the general open question, concerning the minimum cardinality of set of values of the symplectic form on pairs of points in a given set in the plane F 2 (here the set being A × A), see [MPORS,Theorem 4] for a general geometric bound. We formulate the next theorem in slightly more generality.…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…For applications over the prime residue field F p there is the following asymptotic version. See [33,Theorem 8] and [32,Section 3] for its (easy) derivation from Theorem 1.…”
Section: Other Statements Of Theorem 1 and Point-line Incidence Boundmentioning
confidence: 99%
“…Theorem 1 has recently found many applications in sum-product type estimates in, e.g., [38], [3], [33] where the arising sets of points and planes have natural structure of Cartesian products. In particular, in [3,Corollary 6], it was observed that Theorem 1 implied a pointline incidence bound in F 2 in the special case of the point set being a Cartesian product.…”
Section: Other Statements Of Theorem 1 and Point-line Incidence Boundmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that their condition for |A| < p 3/5 can be extended to |A| < p 2/3 , see Remark 10 for more details. See also [12] for variations on the sum-product theorem including sharper results for the few sums many products problem, see [13] for the few products many sums problem and [11] for various other results related to expanders in prime fields.…”
Section: Introductionmentioning
confidence: 99%